Investigation of onboard fuel separation for passenger vehicles. (15th February 2019) - Khan, Ahmad; Morganti, Kai; Sendi, Marwan; Almansour, Mohammed; Hamad, Esam
Abstract: Improving the efficiency of the internal combustion engine will continue to play an important role in reducing greenhouse gas (GHG) emissions in the transport sector. One promising technology that offers improved engine efficiency is the Octane-on-Demand (OoD) concept. This engine-fuel system makes use of two fuels with different octane quality to match the specific anti-knock requirements of the engine under different driving conditions. Previous research has mainly focused on enabling the OoD concept using a two-tank system, whereby the consumer must refuel the vehicle with two different fuels. In this work, a volatility-based flash distillation system is instead utilized to separate a market gasoline (RON 91) into lower-octane and higher-octane fuel streams. Single cylinder engine tests are performed to develop fuel consumption maps for both the separated and unseparated fuels. These maps are then used to evaluate the fuel economy and GHG emissions of a light-duty vehicle across different driving conditions. The fuel separation system is shown to offer improvements in both fuel economy and GHG emissions when compared to the equivalent vehicle utilizing the unseparated market gasoline. This suggests that onboard fuel separation could be an enabling technology for improving the efficiency of future passenger vehicles. Highlights: Onboard fuel separation is examined as an enabler for improving passenger vehicle efficiency. Fuel economy improvements of up to 13% are demonstrated. CO2 emissions improvements of up to 15% are demonstrated. The trade-off between maximizing fuel economy and minimizing CO2 emissions is analyzed. Fuel separation is a promising concept for improving passenger vehicle efficiency.